URGENSI KEARIFAN LOKAL BAGI KEBERLANJUTAN PEMBANGUNAN PERDAMAIAN DI MALUKU PERSPEKTIF FIQH KONTEMPORER - Hasbollah Toisuta; La Jamaa (IAIN Ambon, 2018)
This paper aims to explore and explain the urgency of the values of “local wisdom” for the sustainability of peace building in the Maluku people. Local wisdom is meant in the form of values of living together which are used as moral guidelines for caring for life together across religions and beliefs. While the values of living together can be in the form of expressions that contain the philosophy of social life or values that shape the daily behavior of the community. The values of local wisdom were analyzed based on the perspective of contemporary fiqh. Contemporary fiqh approach here is intended to see to what extent the values contained in local wisdom of the Maluku people have relevance to fiqh and its contextualization in contemporary Maluku society. Based on the results of the research, it was found that the values of local wisdom are still deemed necessary to continue to be developed and become an important part in building peace in Maluku. From the perspective of contemporary fiqh, local traditional values are an important dimension for the dialogue between Islam and local culture. Contemporary fiqh views the local traditional values of the Maluku people as being categorized as 'Urf (known good traditions) that can contribute to peace.Keywords: local wisdom, peace building, contemporary fiqh